Postoperative and Postpartum Onset of Chronic Parkinsonism: Four Case Reports - Ramani B., Manish; Rabin L., Marcie; Kurlan, Roger (International Journal of Medical Students, 2014)
Background: Certain environmental exposures have been linked to the development of parkinsonism. We report four cases in which the onset of chronic parkinsonism occurred immediately or soon after surgery or childbirth. Results: Exposure to certain anesthetic agents in susceptible individuals or the physiological changes associated with surgery or childbirth may have contributed to or precipitated the development of parkinsonism. Conclusion: Clinicians should be aware that postoperative or postpartum settings are potential precipitants of chronic parkinsonism. More research is needed to clarify contributing factors.